Quantity-intensity dynamics of potassium in sunflower (Helianthus annuus)- sorghum (Sorghum bicolor) cropping sequence - Murthy, I.Y.L.N; Muralidharudu, Y; Babu, S.N Sudhakara (The Indian Journal of Agricultural Sciences, 2005)
An experiment was conducted during 2002 to assess quantity-intensity parameters of potassium in red sandy loam (Alfisol) soil for sunflower (Helianthus annuus L.)-sorghum [Sorghum bicolor (L.) Moench] cropping sequence under rainfed condition. Composite samples (0-15 cm depth) of soil were collected after the harvest of rainy-season (kharif sorghum crop from inorganic and organo-inorganic combination fertilized plots of an on-going integrated nutrient-management trial since 1998. Continuous application of inorganic source of 100% recommended dose of fertilization to sunflower and sorghum crops in sequence resulted in relatively higher equilibrium activity ratio for potassium (ARoK) ie (8.6 x 103) than the various inorganic-organic combinations. Labile k (K1) value (0.030) was observed higher in the soil that received 100% recommended dose of fertilizer for sunflower, followed by 50% recommended dose of PK and 50% N through farmyard manure for sorghum. The ARoK correlated positively with shoot (0.532) and seed (0.729) K uptake and sorghum seed yield (0.679). The organo-inorganic treated soils recorded nearly optimum amount of available K comparable to that of only inorganic source of fertilization. Available K status was maintained to meet the K demand of crops over the period under organic-inorganic (50%) combination of fertilization.